Agaricus pocillator, a new record species from Mexico - Chen, J. (2020)
Agaricus is a species-rich genus with nutritional and medicinal interest. Though the taxonomy and phylogeny of the genus have been well advanced during the last decade, the species diversity of the genus has been little studied in Mexico. In the present study, we introduce A.pocillator as a new record species from Mexico based on both morphological characters andmolecular data. The full description, line drawings and photos are provided.